(untitled) (Innovaciones Educativas, 2025)
This research analyzed the didactic strategies used by middle school education chemistry teachers in Costa Rica when addressing the topic of electronic configuration. The study was conducted under a mixed-methods approach, predominantly qualitative, using a concurrent embedded design (QUAL, quan). Information was collected during September and October 2021 using a questionnaire directed at teachers, a survey aimed at students, and the focus group technique. The studied population included 10 teachers and 150 students from four public educational institutions in Costa Rica (Liceo Fernando Volio, Liceo Laboratorio de Liberia, Liceo UNESCO, and Liceo Diurno de Río Frío). It was found that during the pedagogical mediation, students experienced positive emotional states (motivation, excitement, fun) and negative ones (tension, confusion), which affected the teaching-learning process. A high percentage of students reported understanding the topic of electronic configuration and perceived the purpose of the strategies used. It was concluded that the conceptual mastery of teachers when addressing the topic of electronic configuration was adequate and that the most commonly used didactic strategies lacked dynamic components. Additionally, it was concluded that dynamic didactic strategies (use of simulators, applications, and web platforms, among others) are considered appropriate for improving the teaching-learning process, but their implementation is limited by the lack of training and the time constraints faced by teachers.